The First Scube3 Mutant Mouse Line with Pleiotropic Phenotypic Alterations. Issue 12 (1st December 2016) - Fuchs, Helmut; Sabrautzki, Sibylle; Przemeck, Gerhard K H; Leuchtenberger, Stefanie; Lorenz-Depiereux, Bettina; Becker, Lore; Rathkolb, Birgit; Horsch, Marion; Garrett, Lillian; Östereicher, Manuela A; Hans, Wolfgang; Abe, Koichiro; et al.
Abstract: The vertebrate Scube (Signal peptide, CUB, and EGF-like domain-containing protein) family consists of three independent members, Scube1–3, which encode secreted cell surface-associated membrane glycoproteins. Limited information about the general function of this gene family is available, and their roles during adulthood. Here, we present the first Scube3 mutant mouse line (Scube3 N294K/N294K ), which clearly shows phenotypic alterations by carrying a missense mutation in exon 8, and thus contributes to our understanding of SCUBE3 functions. We performed a detailed phenotypic characterization in the German Mouse Clinic (GMC). Scube3 N294K/N294K mutants showed morphological abnormalities of the skeleton, alterations of parameters relevant for bone metabolism, changes in renal function, and hearing impairments. These findings correlate with characteristics of the rare metabolic bone disorder Paget disease of bone (PDB), associated with the chromosomal region of human SCUBE3 . In addition, alterations in energy metabolism, behavior, and neurological functions were detected in Scube3 N294K/N294K mice. The Scube3 N294K/N294K mutant mouse line may serve as a new model for further studying the effect of impaired SCUBE3 gene function.